Analyzing oil production and consumption : asking questions, evaluating evidence, and designing solutions - Steele, Philip, 1948- (Steele, Philip, 1948- Analyzing environmental change., 2019)
Briefly explores the history and origins of concerns about the unsustainable rate at which humans produce and consume oil, and surveys the important questions being asked, how to evaluate the evidence, and how people think about and are coming up with solutions. Includes a glossary.